(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Banks and Banking business has made a drastic transformation in the world. It was in 1904, a cooperative movement started by the Government of India on a cooperative basis in the form of cooperative banks to cope with economically weaker sections of society. Cooperative banks are a small financial institution, which belongs to its members, who are playing dual role as an owner and as a customer. The principle of self-mutual help, democratic management with membership open for all are the basics to design the cooperative structure. These banks are traditionally centered to lend small business and needy borrowers. The present study was conducted to analyze cooperative banks’ lending practices in the Mumbai region (State Maharashtra, Country the India). The research has concluded with suggestions to cooperative banks to improvise lending practices with technological advancement. The present study will help one understand the lending practice of cooperative banks in detail, focusing on Credit Risk Management (CRM).